Paraoxonase-1 activity in patients with cancer: A systematic review and meta-analysis. (July 2018) - Arenas, M.; Rodríguez, E.; Sahebkar, A.; Sabater, S.; Rizo, D.; Pallisé, O.; Hernández, M.; Riu, F.; Camps, J.; Joven, J.
Abstract: Purpose: Paraoxonase-1 (PON1) is a lipolactonase implicated in the elimination of carcinogenic free radicals and in the scavenging mechanisms to maintain oxidative balance. The objective of the present systematic review and meta-analysis was to evaluate possible alterations in serum PON1 activity in patients with cancer. Methods: A systematic search of the observational studies in humans published in the last 15 years was performed through Medline databases following the PRISMA and STARLITE statements. Further, a keyword-based computerized search with restrictions on publication date, and a meta-analysis of case-control studies was performed. Results: In total, 23 studies were included most of which reported decreased PON1 activity in patients with cancer. This could indicate impaired defense ability against oxidative stress with potential implications in cell proliferation, promotion of genetic instability, and alterations in cellular sensitivity to chemotherapy. Conclusion: This systematic review and meta-analysis confirms a consistent association between cancer and decreased serum PON1 activities. These findings may open fruitful lines of research with clinical relevance, and an understanding of molecular alterations underlying carcinogenesis.